Determination of ionic compounds in Antarctic samples using ion-chromatography coupled to mass spectrometry - PADOAN, SARA; BARBARO, ELENA; ZANGRANDO, Roberta; CAPODAGLIO, Gabriele; BARBANTE, Carlo; GAMBARO, Andrea (YISAC 2017, 2017)
The aim of the present work was to develop an analytical method for the quantification of anionic and cationic compounds (Cl-, Br-, I-, NO3-, MSA, SO42-, PO43-, C2-oxalic acid, C2-glycolic acid, C2-acetic acid, C3-malonic acid, cis-usC4-maleic, trans-usC4-fumaric, C4-succinic acid, αC7-benzoic acid, C5-glutaric acid, hC4-malic acid, C6-adipic acid, C7-pimelic acid, Na+, NH4+, K+ and Mg+) to determine their potential sources of input, chemical evolution and transport in aerosol Antarctic samples. We analysed anionic species using ion-chromatography coupled to mass spectrometry and cationic species by capillary ion-chromatography with conductivity detection. The methods were validated through the evaluation of the instrumental linearity, detection limits and instrumental precision; and recovery, accuracy and repeatability of the analytical sample preparation procedure. We determined concentration and particle-size distribution of ionic species from two different Antarctic site: a coastal site near to the Italian Research Station “Mario Zucchelli” and a site located on the Antarctic plateau, close to the Italian-French Research Station “Concordia”. We evaluated possible sources of marine aerosol and behaviour during long distance transport. Aerosol, from the coastal site, was mainly characterized by sea salt species such as Na+, Mg2+, SO42-. These species were mainly distributed in the coarse fraction, confirming the presence of primary aerosol near the ocean source. Aerosol collected over the Antarctic plateau was characterized by species as nss-SO42-, NO3- and methanesulfonic acid. These species were mainly distributed in the fine fraction, highlighting a behaviour of a typical secondary aerosol, where several chemical and physical processes occurred.